The Computational Prediction Methods for Linear B-cell Epitopes - Jia, Cangzhi; Gong, Hongyan; Zhu, Yan; Shi, Yixia (Current Bioinformatics, 2019)
Background: B-cell epitope prediction is an essential tool for a variety of immunological studies. For identifying such epitopes, several computational predictors have been proposed in the past 10 years. Objective: In this review, we summarized the representative computational approaches developed for the identification of linear B-cell epitopes. Methods: We mainly discuss the datasets, feature extraction methods and classification methods used in the previous work. Results: The performance of the existing methods was not very satisfying, and so more effective approaches should be proposed by considering the structural information of proteins. Conclusion: We consider existing challenges and future perspectives for developing reliable methods for predicting linear B-cell epitopes.
Keywords: linear B-cell epitopes